The Role of Mangroves in Retaining Penaeid Prawn Larvae in Klang Strait, Malaysia - Chong, V.C.; Sasekumar, A.; Wolanski, E. (Kluwer (now part of Springer), 1996)
The mangrove-fringed Klang Strait, Malaysia, retains approximately 65 billion penaeid prawn larvae annually prior to their settlement in coastal nursery grounds. This phenomenon appears to be due principally to tidal currents and lateral trapping in mangrove-fringed channels, the wind playing an insignificant role.